MANAJEMEN HUMAS: MEMBANGUN PERAN MASYARAKAT PADA LEMBAGA PENDIDIKAN - Fajri Dwiyama; Adriani Adriani; Ismia Ismia; Riska Oktafiana (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2020)
The community is one of the main keys in developing educational institutions. High public participation in educational institutions, it is not impossible to deliver educational institutions to become quality institutions, still exist in the midst of competition between educational institutions, and become the most favorite institution in the community. This can be achieved if all stakeholders in educational institutions also exist in advancing the institution, in relation to the community. PR has a very big war in realizing this, but the facts show that most educational institutions have PR but have not been able to get people to participate in advancing education. This study aims to find out how much the role of stakeholders in educational institutions in building public relations, especially in Madrasah Aliyah Negeri 1 Bone, and further to find out what participation is given by the community for the advancement of these educational institutions. The method used in this research is a qualitative case study. The results obtained showed that Madrasah Aliyah Negeri 1 Watampone, which implemented good public relations management, was able to make the community participate in advancing education at the institution.